Bilateral Foreign Direct Investment Flows in Similar Islamic Countries: Alternative Explanation for Gross Domestic Product Per Capita Difference Effect - Kaukab, M. Elfan; Anggara, Ali Akbar; Jusoh, Wan Noor Hazlina Wan (LP3M Universitas Putra Bangsa, 2025)
This study examines whether developed Islamic countries invest in developing Islamic countries through Foreign Direct Investment (FDI), motivated by common religion and economic diplomacy. Using bilateral data from 2001–2012, it finds that FDI flows are positively influenced by GDP per capita differences and the geographic disadvantage of landlocked countries. However, diplomatic presence and regional trade agreements do not show a significant effect. The findings suggest that common religion, rather than diplomacy, psychologically influences FDI decisions.